2020
DOI: 10.1002/trc2.12013
|View full text |Cite
|
Sign up to set email alerts
|

A precision medicine framework using artificial intelligence for the identification and confirmation of genomic biomarkers of response to an Alzheimer's disease therapy: Analysis of the blarcamesine (ANAVEX2‐73) Phase 2a clinical study

Abstract: Introduction:The search for drugs to treat Alzheimer's disease (AD) has failed to yield effective therapies. Here we report the first genome-wide search for biomarkers associated with therapeutic response in AD. Blarcamesine (ANAVEX2-73), a selective sigma-1 receptor (SIGMAR1) agonist, was studied in a 57-week Phase 2a trial (NCT02244541).The study was extended for a further 208 weeks (NCT02756858) after meeting its primary safety endpoint. Methods: Safety, clinical features, pharmacokinetic, and efficacy, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 58 publications
(52 reference statements)
0
41
0
Order By: Relevance
“…Multiple gastric cancer trials excluded patients with a history of cancer from the eligible cohort. In contrast, some trials did not exclude or mention this group of patients 7,9,10,29,30 . We found that prior cancer exerted completely different impacts on the survival prognosis depending on the different prior cancer types.…”
Section: Discussionmentioning
confidence: 66%
“…Multiple gastric cancer trials excluded patients with a history of cancer from the eligible cohort. In contrast, some trials did not exclude or mention this group of patients 7,9,10,29,30 . We found that prior cancer exerted completely different impacts on the survival prognosis depending on the different prior cancer types.…”
Section: Discussionmentioning
confidence: 66%
“…AI/ML approaches have also been applied to drug response studies to treat AD patients in a more precise, personalized way. Hampel et al 429 has built an AI/ML‐based precision medicine framework for identifying the genomic biomarkers of response to AD therapy. Specifically, they studied blarcamesine (ANAVEX2‐73), a selective sigma‐1 receptor agonist, in a Phase 2a trial, where they obtained the patients' whole‐exome and transcriptome data and recorded the measures of safety, clinical features, pharmacokinetics, and efficacy.…”
Section: Ai/ml Applications In Cns Drug Discoverymentioning
confidence: 99%
“…The second is that an effective biomarker must be defined during clinical trials in order to adjust the most effective dose. For instance, Hampel et al [161] recently described that patients with S1R wildtype phenotype and high blarcamesine plasma concentration after IV administration showed the best stabilization of ADCS-ADL and MMSE scores after 162 weeks of barcamesine. No association with more classical biomarkers has been proposed yet.…”
Section: Expert Opinionmentioning
confidence: 99%